Maternal and Perinatal Outcomes and Associated Risk Factors in Women Undergoing More Than Five Cesarean Sections - Komal, Sanila Gul, Saima Ahmed (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To examine the maternal and neonatal outcomes in patients who were received more than fifth C-section also examines the associated risk factors. Study Design: Case control Place & Duration: Bacha Khan Medical Complex Swabi from Jan 2023 to June 2023. Materials and Methods: Total 100 patients with ages 20 to 50 years and gestation age >32 weeks were included in this study. Patient’s demographical detail including age, residence, education and socioeconomic status were recorded after written consent. All the patients were divided into two groups; Group A consist of 50 patients and had undergoing fifth or more C-section delivery and Group B with 50 patients who had received less than 5th C-section. Intra and post-operative complications were recorded. Neonatal outcomes such as admission to NICU, birth weight, Apgar score and mortality were recorded. Compare the results between both groups. Results: In Group A, the incidence of extensive adhesion was high 21 (42%) patients as compared to Group B 10%. Bowel injury found in 3 (6%) patients in Group A while no patient in Group B. Placenta previa found in 6 (12%) in Group A and 1 (2%) patients in Group B. Need of blood transfusion rate was high in Group A 24% as compared to Group B 8%. In Group A 30% neonates need to NICU. Low birth weight was higher in Group A patients. 2% neonatal death was recorded in Group A while none in Group B. Conclusion: Patients with fifth or more C-sections had high risk of maternal and neonatal morbidity. Patients should aware about the adverse outcomes of repeated C-section deliveries. Keywords: C-sections, Maternal outcomes, Neonatal, Morbidity, Mortality